KOHESI GRAMATIKAL DAN LEKSIKAL PADA LIRIK LAGU “KITA” GROUP BAND SHEILA ON 7 - Pramitasari, Afrinar (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to describe (1) how the form of grammatical cohesion in the lyrics of the song "Kita" Group Band Sheila on 7, and (2) how the form of lexical cohesion in the lyrics of the song "Kita" Group Band Sheila on 7. This type of research is descriptive qualitative. . The research data is in the form of fragments of the lyrics of the song "Kita" which contains aspects of grammatical and lexical cohesion. The data collection technique used is the listening and note-taking technique. The data analysis technique used is the Miles and Huberman interactive model. The results showed 1) there were aspects of grammatical cohesion in the form of references (references), substitutions, and conjunctions, 2) found that there were aspects of lexical cohesion in the form of synonyms, antonyms, hyponyms, and repetitions. The types of references found are in the form of personal and demonstrative references, while the types of conjunctions found are coordinating and subordinating conjunctions. The types of repetition found in the lyrics of the song "Kita" are anadiplosis, mesodiplosis, tautoris, and epizeuksis repetitions. From the results of data analysis, the researcher concludes that the lyrics of the song "Kita" Sheila on7 have fulfilled the elements of discourse integrity both lexically and grammatically.Keywords: Cohession, Lexical, Grammatical, Song Lyrics